The magnetic early B-type Stars II: stellar atmospheric parameters in the era of Gaia. Issue 2 (11th February 2019) - Shultz, M E; Wade, G A; Rivinius, Th; Alecian, E; Neiner, C; Petit, V; Wisniewski, J P; ,
Abstract: Atmospheric parameters determined via spectral modelling are unavailable for many of the known magnetic early B-type stars. We utilized high-resolution spectra together with non-local thermodynamic equilibrium models to measure effective temperatures T eff and surface gravities log g of stars for which these measurements are not yet available. We find good agreement between our T eff measurements and previous results obtained both photometrically and spectroscopically. For log g, our results are compatible with previous spectroscopic measurements; however, surface gravities of stars previously determined photometrically have been substantially revised. We furthermore find that log g measurements obtained with HARPSpol are typically about 0.1 dex lower than those from comparable instruments. Luminosities were determined using Gaia Data Release 2 parallaxes. We find Gaia parallaxes to be unreliable for bright stars ( V < 6 mag) and for binaries; in these cases we reverted to Hipparcos parallaxes. In general, we find luminosities systematically lower than those previously reported. Comparison of log g and log L to available rotational and magnetic measurements shows no correlation between either parameter with magnetic data, but a clear slow-down in rotation with both decreasing log g and increasing log L, a result compatible with the expectation that magnetic braking should lead to rapid magnetic spin-down that accelerates with increasing mass-loss.